Combined use of remote sensing data and geographic information system techniques for detecting underground structures for defense and security applications in Cyprus - Melillos, George; Hadjimitsis, Diofantos G.; Michaelides, Silas (My University, 2019)
The purpose of this paper is to present the combined use of Remote Sensing (RS) data and Geographic Information System (GIS) techniques for detection of military underground structures in Cyprus. The combination of RS data and GIS tools for detecting these types of structures entails some benefits, such as accessibility, accuracy, easy collection of data, rapid production of maps and better decision-making. In this study, Sentinel-2A satellite images have been used in order to detect underground structures. Atmospheric correction was performed using the Sen2cor plugin in Sentinel Application Platform (SNAP). In addition, maps of vegetation indices throughout the plants' phenological development cycle were generated in ArcGIS, for: NDVI (Normalized Difference Vegetation Index), SR (Simple Ratio), DVI (Difference Vegetation Index), GEMI (Global Environment Monitoring Index), RDVI (Renormalized Difference Vegetation Index) and EVI (Enhanced Vegetation Index). The measurements were taken at two test sites: Area (a) comprises a vegetated area covered with barley, in the presence of an underground military structure, and Area (b) a vegetated area covered with barley, in the absence of an underground military structure.
Keywords: Atmospheric correction; GIS; Military underground structures; Remote Sensing; Sentinel-2A; Vegetation indices